Memorizing Habits Model in Muhammadiyah 3 Waru Junior High School - Noer Viatah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
AbstractThis study aims to describe memorizing habits model in Muhammadiyah 3 Waru Junior HighSchool. This research is intended to provide an overview for the memorizers of Qur'an regarding memorizing method that can provide assistance in reducing any difficulties in memorizing the Qur'an. The type of research used is field research with a qualitative approach. The data collection techniques are by observation, interviews, and documentation. The results of this study states that the memorizing habits model can run smoothly with Tikrar learning method and several other strategies. Habits model is carried out in a fun classical way so students do not get bored and feel burdened when memorizing. Habits model that has been carried out at Muhammadiyah 3 Waru Junior HighSchool is Tikrar (repetition) method, the Qur'an friendship, and tahfidz Qur'an. Keywords: models of habituation, memorization, pledge, Qur'an, tahfidz, learning, adventure, qualitative approaches.